2015
DOI: 10.1177/1086026615622028
|View full text |Cite
|
Sign up to set email alerts
|

Industries Regulation and Firm Environmental Disclosure: A Stakeholders’ Perspective on the Importance of Legitimation and International Activities

Abstract: The potential negative environmental consequences of the activities of international firms has been scrutinized. In response to these pressures, international firms have started to disclose (voluntarily or not) environmental information in order to increase transparency and ensure legitimacy. While several factors have been pointed out as the drivers of such disclosing behavior, the role of industrial regulation has remained underesearched. To better understand this challenge, we rely on a sample of 1,150 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 79 publications
(128 reference statements)
4
30
1
1
Order By: Relevance
“…Moreover, home (or foreign) countries' legal and ethical regulations also influence their legitimization with foreign (or home) countries' social values and expectations (Faller and Zu Knyphausen-Aufseß 2016). Additionally, foreign investors concerned with environmental issues will influence domestic companies' management to comply with environmental regulations and disclose more ESRP information to minimize political costs (Gamerschlag et al 2011;Delgado-Márquez et al 2016).…”
Section: Foreign Ownershipmentioning
confidence: 99%
“…Moreover, home (or foreign) countries' legal and ethical regulations also influence their legitimization with foreign (or home) countries' social values and expectations (Faller and Zu Knyphausen-Aufseß 2016). Additionally, foreign investors concerned with environmental issues will influence domestic companies' management to comply with environmental regulations and disclose more ESRP information to minimize political costs (Gamerschlag et al 2011;Delgado-Márquez et al 2016).…”
Section: Foreign Ownershipmentioning
confidence: 99%
“…Moreover, organizations work in a challenging and competitive environment and receive significant pressures from strong environmental groups investing in environmental projects [13]. Furthermore, strong national and international environmental groups, international donor agencies, and funding organizations encourage organizations to invest in the area of environmental pollution, environmental innovation, green products, environmental management system, and appropriate utilization of natural resources [7,9,12]. As a result of multi-stakeholder pressures, banking companies are reporting more green information and launching more green products to protect their investment and reputation as well as to improve customer satisfaction.…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…Cheng et al [48] argued that companies disclosing more CSR information face lower capital constraints, which leads better stakeholder engagement and transparency. Prior research identified that different regulations have played significant roles in green reporting, green innovation, and the green movement in developed and developing countries [12,48]. Ortiz-de-Mandojana et al [16] conducted research on 210 firms in 14 countries in North America and Europe and documented that institutional cognitive and normative pressures aid environmental reporting of the region while coercive pressures discourage environmental reporting.…”
Section: Developed Countries Green Regulationmentioning
confidence: 99%
“…Therefore, the organization's disclosure practices have a potential to create value to society. By disclosing economic, environmental, and social information, the organization may communicate with different types of potential parties including suppliers, creditors, activist groups, the government, the media, customers as well as the general public [3,29,38,39]. According to the signaling theory, sustainability disclosure sends different signals to the market and receives responses back from the market.…”
Section: Introductionmentioning
confidence: 99%